Helping your clients and patients take ownership over their exercise: Fostering exercise adoption, adherence, and associated well-being - Edmunds, J.; Ntoumanis, Nikos; Duda, J. (2009)
LEARNING OBJECTIVE: This feature article emphasizes the need for physical activity and exercise interventions to be developed and delivered in accordance with psychological theory. Pulling from a contemporary theory of human motivation called Self-determination Theory, this article demonstrates how delivering an exercise message, consultation, or program in an autonomy-supportive, well-structured, and interpersonally involved way may benefit participants' attempts to become and stay more active. Practical strategies that may be used by a health and fitness professional to create an autonomy-supportive, well-structured, and interpersonally involved exercise environment also are presented. Copyright © 2009 Lippincott Williams & Wilkins.